Urbane Produktion und temporäre räumliche Nähe in Produktionsprozessen - Butzin, Anna; Meyer, Kerstin (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
This article argues that temporary spatial proximity between economic agents can also have a productionrelated purpose besides knowledge generation. At the same time, due to new technological developments and trends, consumer goods are generated by temporary spatial proximity between end customers and producers. The purpose of the temporary exchange is to create material goods meeting the individual demands of the respective customer in real time. The aim of this paper is to analyse production-related temporary spatial proximity of urban manufacturing to show how production sites and locations as well as the relationship with customers are altered. Based on a literature analysis and case studies, production-related temporary spatial proximity in large companies, factories, makerspaces and festivals is examined. The results show that customers are intensively involved in the production process. Changes in the production method and location are the consequence, since it is about the production of individual pieces. In addition, production locations change, as they need to be in retail locations or housing areas, i.e. close to the market where the end consumers are. Production-oriented temporal spatial proximity between producers and consumers and associated inner-city production will not replace mass production of consumer goods. However, it is an important factor influencing the choice of business models and business locations for entrepreneurs given the current trend in the individualisation of consumer goods.
Keywords: Co-production; Temporary spatial proximity; Urban manufacturing